Two-phase bimetallic carbide heterostructure electrocatalyst and preparation method and application thereof
By preparing a two-phase bimetallic carbide heterostructure WMoC2/WVC2 electrocatalyst, the problems of high cost of precious metal-based electrocatalysts and poor stability of transition metal compounds were solved, and efficient electrocatalytic water splitting performance in an alkaline environment was achieved.
Patent Information
- Application Number
- CN202511046993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-10-21
AI Technical Summary
The high cost and low element abundance of existing precious metal-based electrocatalysts limit their widespread application. The low conductivity and poor electrochemical reaction stability of transition metal compounds in aqueous solutions lead to unsatisfactory activity and long-term stability in electrocatalytic water splitting.
A two-phase bimetallic carbide heterostructure WMoC2/WVC2 electrocatalyst was prepared by a step-by-step hydrothermal and solid-phase reaction method. By introducing the synergistic effect of the two components, the electronic structure of the material was optimized and the reaction active sites were increased, thereby improving the electrocatalytic activity and stability.
It exhibits good electrocatalytic activity in an alkaline environment, significantly reduces the water splitting overpotential, improves the stability and catalytic performance of the electrocatalyst, and is suitable for the field of electrocatalytic water splitting.
Smart Images

Figure CN120818852A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials and relates to a two-phase bimetallic carbide heterostructure electrocatalyst and a preparation method and application thereof. Background Art
[0002] As an ideal alternative to traditional fossil fuels, hydrogen has attracted considerable attention due to its high energy density, zero pollution emissions, and recyclability. Among various hydrogen production methods, electrocatalytic water splitting offers a sustainable, economical, and environmentally friendly approach. Furthermore, this process can be closely integrated with intermittent renewable energy and green energy storage and conversion, forming a sustainable energy cycle.
[0003] However, in practical applications, due to the high overpotential of the half-reaction, a large amount of additional electrical energy is consumed to overcome the reaction barrier in the water splitting process. Therefore, designing efficient electrocatalysts is crucial to improving the kinetics of electrocatalytic reactions. So far, noble metal electrocatalysts based on platinum group metals (PGMs), such as Pt and Ru, have shown excellent efficiency and stability. However, the high cost and low element abundance of noble metal-based electrocatalysts limit their widespread application and prevent large-scale industrial production. Therefore, the development of low-cost non-noble metal (NPM) electrocatalysts with significant catalytic performance, such as transition metal compounds for HER (hydrogen evolution reaction) and OER (oxygen reduction reaction), has become an urgent challenge. Although significant progress has been made in this field, the problems of low conductivity and poor electrochemical reaction stability of transition metal compounds in aqueous solution still exist, resulting in unsatisfactory activity and long-term stability.
[0004] As research gradually deepens, transition metal carbides (TMCs) have become a strong candidate with the potential to replace precious metal-based catalysts. As an electrocatalytic water splitting catalyst, TMC shows significant advantages in mechanical stability, chemical stability and corrosion resistance under electrochemical conditions. Due to the hybridization between the carbon orbitals and metal atomic orbitals in TMC, TMC has an electronic structure similar to Pt, which optimizes the adsorption of key intermediates in the HER process, showing the potential to overcome the above problems and has been proven to be highly active and stable for water splitting. Although it has excellent performance close to that of precious metal catalysts in theory, the catalytic ability of single-phase TMC is actually unsatisfactory. This is mainly due to the strong hydrogen bonding on the metal atoms, which slows down the overall water splitting kinetics. In particular, in alkaline media, the excessive hydrogen evolution Gibbs free energy (ΔGH*) significantly hinders the desorption of H2 in the HER process. In order to achieve industrial application and replace precious metal-based catalysts, further modification treatments such as interface engineering are still required.
[0005] Bimetallic carbides, also defined as interstitial compounds, are actually solid solutions in which solute metal elements (e.g., Co / Ni / Fe / Zn / Ta / W / Mo) can be introduced into single-crystalline carbides. Bi-TMCs typically exhibit specific crystalline bimetallic carbides (Bi-TMCs), which play a crucial role in enhancing the electrocatalytic activity of TMC electrocatalysts. The introduction of additional transition metals to form bimetallic carbides has a significant impact on optimizing intrinsic catalytic performance. By increasing the degree of coordination unsaturation of surface metal atoms, the active site density increases by 2-3 orders of magnitude, while also improving the internal conductivity of the material and modulating the electronic structure of the relevant active sites, inducing a shift of the d-band center toward the Fermi level. Generally, the introduction of late transition metals with internal paired d electrons into early transition metal carbides can induce a redistribution of valence electrons, significantly optimizing the latter's electronic structure and, consequently, enhancing catalytic activity due to the "3d electron complementarity effect." Furthermore, the Gibbs free energy of hydrogen evolution at the reaction sites of the bimetallic carbide can be adjusted to a moderate level, thereby promoting the water splitting process. In recent years, researchers have discovered that bimetallic carbides not only exhibit excellent HER activity but also possess a stronger ability to regulate valence electron density due to their inherent structure (containing electron-rich transition metals and electron-deficient transition metals). Compared with traditional transition metal carbides, bimetallic carbides have higher metal-metal interactions and structural stability, and can better withstand highly corrosive acidic and alkaline media. Their stable structure helps resist deactivation of the active sites of corrosive reaction catalysts, thereby improving the long-term stability of the catalyst.
[0006] Heterostructure construction has a significant impact on the electrocatalytic hydrogen evolution reaction (HER), primarily through interface engineering, electronic structure manipulation, and synergistic effects that enhance catalytic performance. It is widely used in the preparation of electrocatalytic materials. Charge redistribution and d-band center realignment at the heterostructure interface can optimize the hydrogen adsorption free energy (ΔGH*). Different components within the heterostructure can individually optimize the H adsorption and H2 desorption processes, modulating the adsorption strength of the metal-optimized intermediate (H*) toward the kinetic optimum (ΔGH*≈0). Furthermore, lattice distortions and defects at the heterostructure interface can serve as highly active sites, increasing the reactive surface area. Summary of the Invention
[0007] To address the above issues, the present invention aims to provide a two-phase bimetallic carbide heterostructure electrocatalyst, its preparation method, and its application. The present invention prepares a bimetallic heterostructure WMoC2 / WVC2 electrocatalytic hydrogen evolution material via a step-by-step hydrothermal and solid-phase reaction method. This preparation method is environmentally friendly and pollution-free, has low raw material costs, and exhibits excellent electrocatalytic activity in alkaline environments. The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a two-phase bimetallic carbide heterostructure electrocatalyst. The composition of the two-phase bimetallic carbide heterostructure electrocatalyst is WMoC2 / WVC2, wherein preferably, the mass percentages of WMoC2 and WVC2 are 40% to 80% and 20% to 60%, respectively.
[0009] In a second aspect, the present invention provides a method for preparing a two-phase bimetallic carbide heterostructure electrocatalyst. The preparation method comprises the following steps: Step (1) dispersing a vanadium source, a molybdenum source and a tungsten source in a solvent to obtain a solution A; Step (2) uniformly mixing cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, glucose and solution A to obtain solution B; Step (3) subjecting solution B to a hydrothermal reaction to obtain product C; In step (4), the product C is mixed evenly with a carbon source and then calcined to obtain a two-phase bimetallic carbide heterostructure electrocatalyst.
[0010] Preferably, in step (1), the vanadium source is at least one of ammonium metavanadate, vanadium acetylacetonate, vanadium chloride or a hydrate thereof; the molybdenum source is at least one of molybdenum pentachloride, ammonium molybdate, sodium molybdate or a hydrate thereof; and the tungsten source is at least one of ammonium tungstate, ammonium paratungstate, tungsten chloride, sodium tungstate or a hydrate thereof.
[0011] Preferably, in step (1), the molar ratio of tungsten to vanadium to molybdenum in the tungsten source, the vanadium source and the molybdenum source is 1:1:1 to 6:1:1.
[0012] Preferably, in step (2), the molar ratio of cetyltrimethylammonium bromide to cetyltrimethylammonium chloride is 1:1 to 1:4; and the molar ratio of the total molar amount of cetyltrimethylammonium bromide and cetyltrimethylammonium chloride to glucose is 0.3 to 0.5:0.5 to 1.
[0013] Preferably, in step (3), the temperature of the hydrothermal reaction is 150-200° C., and the time is 12-24 hours.
[0014] Preferably, in step (4), the calcination temperature is 600-900° C., the calcination time is 2-6 hours, and the calcination atmosphere is argon.
[0015] Preferably, in step (4), the carbon source is at least one of melamine, urea and dicyandiamide.
[0016] Preferably, the vanadium source in step (1) and the carbon source in step (4) have a vanadium-to-carbon molar ratio of 1:10 to 1:1500, preferably 1:50 to 1:900.
[0017] In a third aspect, the present invention provides the use of the two-phase bimetallic carbide heterostructure electrocatalyst in the preparation of a hydrogen evolution electrode.
[0018] The present invention has the following beneficial effects:
[0019] 1. The present invention adopts a step-by-step hydrothermal combined with a solid-phase method to prepare WMoC2 / WVC2 electrocatalytic materials. The process is simple and easy, the operation is convenient, the preparation process is green and environmentally friendly, and no complex synthesis equipment is required. The obtained catalyst has good catalytic stability.
[0020] 2. The WMoC2 / WVC2 electrocatalytic material prepared by the present invention introduces a dual-component synergistic effect into the transition metal carbide, optimizes the electron density around the d-band center and metal center of the material, and the electron transport in the electrocatalyst, optimizes the hydrogen adsorption free energy, and increases the reaction active sites, thereby improving the intrinsic activity and playing a vital role in enhancing the HER mechanism.
[0021] 3. The bimetallic carbide heterostructure WMoC2 / WVC2 electrocatalytic hydrogen evolution material prepared by this invention further optimizes the electronic structure and surface properties of the transition metal carbide through the rational design of the heterostructure, thereby improving its activity and stability. It exhibits excellent catalytic performance under alkaline conditions and also exhibits excellent electrocatalytic hydrogen evolution performance at high current densities. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the X-ray diffraction pattern of the WMoC2 / WVC2 electrocatalytic material prepared in Example 1; Figure 2 1 is a graph showing the electrocatalytic hydrogen evolution performance of the WMoC2 / WVC2 electrocatalytic material prepared in Example 1; Figure 3 is a scanning electron microscope image of the WMoC2 / WVC2 electrocatalytic material prepared in Example 1; Figure 4 This is a transmission electron micrograph of the WMoC2 / WVC2 electrocatalytic material prepared in Example 1. DETAILED DESCRIPTION
[0023] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not intended to limit the present invention. The following is an exemplary description of the preparation method of the bimetallic heterostructure WMoC2 / WVC2 electrocatalytic material.
[0024] A vanadium source, a molybdenum source, and a tungsten source are dispersed in a solvent to obtain a solution A. The vanadium source includes, but is not limited to, at least one of ammonium metavanadate, vanadyl acetylacetonate, vanadium chloride, or hydrates thereof. The molybdenum source includes, but is not limited to, at least one of molybdenum pentachloride, ammonium molybdate, sodium molybdate, or hydrates thereof. The tungsten source includes, but is not limited to, at least one of ammonium tungstate, ammonium paratungstate, tungsten chloride, sodium tungstate, or hydrates thereof.
[0025] In some embodiments, the molar ratio of tungsten, vanadium, and molybdenum in the tungsten source, vanadium source, and molybdenum source is 1:1:1 to 6:1:1. If the molar ratio of the tungsten source, vanadium source, and molybdenum source in the reaction system is not appropriate, the three substances will be out of balance during the reaction, and the excess free metal ions will not be able to fully participate in the complex reaction. These impurities are difficult to eliminate during solid-phase sintering, resulting in residual oxides or the formation of single metal carbides. This is because: during the hydrothermal process, the metal precursor needs to go through a "dissolution-crystallization" process to form a uniform complex. When the metal source ratio is unbalanced, the difference in the dissolution rate of different metal ions will lead to local supersaturation and trigger non-uniform nucleation, which will cause the crystal size distribution to become wider and the degree of alloying of the material to be reduced, thereby affecting the formation of heterogeneous structures and preventing the formation of the target bimetallic carbide. At the same time, in the hydrothermal reaction, glucose and the template (cationic surfactant) rely on the charge balance of the metal ions to achieve uniform coating, and the glucose-derived carbon layer needs to uniformly coat the metal core. An imbalance in the metal source ratio can also lead to excessively high local metal concentrations, exposing some metal. During calcination, the exposed metal is more likely to sinter and grow, reducing active sites. The carbon mesh coating on the surface of the bimetallic heterostructure WMoC2 / WVC2 particles can improve the material's electrical conductivity, significantly enhancing the efficiency of the hydrogen evolution reaction and promoting a reduction in the hydrogen overpotential of electrocatalytic water splitting. Preferably, the molar ratio of tungsten to vanadium to molybdenum is 1.2:1:1 to 6:1:1.
[0026] The solvent includes, but is not limited to, water and / or ethanol. In an optional embodiment, the concentration of the vanadium source in solution A may be 1 to 100 mmol / L, the concentration of the molybdenum source may be 1 to 100 mmol / L, and the concentration of the tungsten source may be 1 to 100 mmol / L. In an optional embodiment, the concentration of the vanadium source in solution A may be 1 to 50 mmol / L, the concentration of the molybdenum source may be 1 to 50 mmol / L, and the concentration of the tungsten source may be 1 to 50 mmol / L.
[0027] Cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and glucose are added to solution A and mixed evenly to obtain solution B. In the hydrothermal synthesis, cetyltrimethylammonium bromide (CTAB) and cetyltrimethylammonium chloride (CTAC) can be used as dispersants. The synergistic effect of the two significantly improves the morphology control and dispersion stability of the bimetallic carbide heterostructure. Glucose can coat the metal particles in the hydrothermal reaction and form a uniform carbon coating layer in combination with the dispersant. At the same time, it provides binding sites for metal ions, preliminarily forms a carbon-metal complex, and provides a basis for the solid-phase transformation of the bimetallic carbide. In solution B, the concentration of cetyltrimethylammonium bromide can be 1-100 mmol / L, the concentration of cetyltrimethylammonium chloride can be 1-100 mmol / L, and the concentration of glucose can be 1-100 mmol / L. In an optional embodiment, the concentration of cetyltrimethylammonium bromide in solution B may be 1 to 50 mmol / L, the concentration of cetyltrimethylammonium chloride may be 1 to 50 mmol / L, and the concentration of glucose may be 1 to 50 mmol / L.
[0028] For example, the molar ratio of cetyltrimethylammonium bromide to cetyltrimethylammonium chloride is 1:1 to 1:4. In some other embodiments, the molar ratio of the total molar amount of cetyltrimethylammonium bromide and cetyltrimethylammonium chloride to glucose is 0.3-0.5:0.5-1.
[0029] Solution B is subjected to a hydrothermal reaction to obtain product C. The temperature of the hydrothermal reaction can be 150-200°C, and the time can be 12-24 hours. The hydrothermal reaction generates a bimetallic carbon precursor and promotes metal complexation. In the hydrothermal system, the uniform dissolution, controllable reduction and directional crystallization of the metal precursor are achieved through the high temperature and high pressure liquid phase environment, while promoting the pyrolysis and carbonization of the carbon source (glucose), thereby promoting the nucleation and growth of the bimetallic carbide heterostructure (WVC2 / WMoC2).
[0030] After the product C is evenly mixed with the carbon source and calcined, a two-phase bimetallic carbide heterostructure electrocatalyst is obtained. The carbon source includes but is not limited to at least one of melamine, urea, and dicyandiamide. The vanadium-carbon molar ratio of the vanadium source and the carbon source is 1:10 to 1:1500, preferably 1:50 to 1:1000. When the carbon source ratio is lower than this range, the precursor will not react completely, resulting in residual oxides. An excessive carbon source ratio causes the material morphology to agglomerate, thereby reducing the catalytic performance of the material. In an optional embodiment, the vanadium-carbon molar ratio of the vanadium source and the carbon source is 1:150 to 1:1000.
[0031] For example, the calcination temperature may be 600 to 900° C., the calcination time may be 2 to 6 hours, and the calcination atmosphere may be argon.
[0032] The following is an illustrative example of a method for preparing a bimetallic heterostructure WMoC2 / WVC2 electrocatalytic material.
[0033] Weigh 1-2 mmol of ammonium metavanadate (NH4VO3), 0.5-2 mmol of molybdenum pentachloride (MoCl5), 0.05-0.5 mmol of ammonium paratungstate (NH4 10 W 12 O 41 ·xH2O), maintaining the molar ratio of tungsten, vanadium and molybdenum at (W:V:Mo=1:1:1~6:1:1), and dissolving them in a mixed solution of 50~200ml of water and ethylene glycol (volume ratio is 1:0.05~1:0.5), which is recorded as solution A.
[0034] 0.1-0.5 mmol hexadecyltrimethylammonium bromide (CTAB), 0.1-0.5 mmol hexadecyltrimethylammonium chloride (CTAC), 0.5-1 mmol glucose (C6H 12 O6) was added to solution A, heated and stirred at 60°C in a water bath for 12 to 24 hours, and ultrasonicated for 30 minutes to obtain solution B. The molar ratio of hexadecyltrimethylammonium bromide to hexadecyltrimethylammonium chloride was 1:1 to 1:4.
[0035] Transfer the prepared solution B into a polytetrafluoroethylene hydrothermal autoclave with a filling (volume) ratio of 20% to 70%. Set the oven temperature to 150 to 200°C and the reaction time to 12 to 24 hours. After the reaction is completed, collect the material in the autoclave, wash and dry it to obtain powder C.
[0036] Take the powder C obtained in the above step, weigh 0.05-0.5 mol of melamine (C3H6N6), ensure that the vanadium-carbon molar ratio of the vanadium source and the carbon source is 1:10-1:1500, fully mix it with the powder C by mechanical mixing, transfer it to a low-temperature tubular furnace, and calcine it under an argon atmosphere at a heating rate of 5-10°C / min and a set temperature of 600-900°C. After keeping warm for 2-6 hours, cool it naturally to obtain WMoC2 / WVC2 electrocatalytic material.
[0037] In summary, the present invention prepares WMoC2 / WVC2 material by combining hydrothermal and solid-phase reaction methods. The prepared electrocatalytic material has excellent hydrogen evolution catalytic performance and can be applied in the field of electrocatalytic water splitting.
[0038] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description herein, and are not limited to the specific numerical values exemplified below.
[0039] Example 1
[0040] The preparation method of a two-phase bimetallic carbide heterostructure hydrogen evolution electrocatalyst comprises the following steps:
[0041] 1) Weigh 1 mmol of ammonium metavanadate, 1 mmol of molybdenum pentachloride, and 0.1 mmol of ammonium paratungstate and dissolve them in a mixed solution of water and ethylene glycol (volume ratio of 1:0.05, 50 ml), which is recorded as solution A.
[0042] 2) Add 0.15 mmol of hexadecyltrimethylammonium bromide, 0.15 mmol of hexadecyltrimethylammonium chloride, and 0.6 mmol of glucose to solution A, heat and stir at 60°C in a water bath for 24 h, and ultrasonicate for 30 min to obtain solution B.
[0043] 3) The prepared solution B was transferred into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 70%, the hydrothermal temperature was set to 180°C, and the reaction time was 12 hours. After the reaction was completed, the material in the reactor was collected, washed and dried to obtain powder C.
[0044] 4) Take the powder C obtained in the above step, weigh 0.3 mol of melamine (C3H6N6), fully mix it with powder C by mechanical mixing, transfer it to a low-temperature tubular furnace, and calcine it under argon atmosphere at a heating rate of 5°C / min and a set temperature of 600°C. After keeping warm for 3 hours, cool it naturally to obtain the WMoC2 / WVC2 electrocatalytic material.
[0045] Figure 1This is the XRD pattern of WMoC2 / WVC2 electrocatalytic material. The characteristic peaks at 36.807°, 42.760°, 62.069°, 74.391°, and 78.310° in the figure correspond to the (111), (200), (220), (311), and (222) crystal planes of WVC2 (PDF#65-8826), respectively; while the characteristic peaks at 31.658°, 35.709°, 48.457°, 64.154°, 66.122°, 73.312°, 75.644°, and 77.481° in the figure correspond to the (001), (100), (101), (110), (002), (111), (200), and (102) crystal planes of WMoC2 (PDF#65-8770), indicating that the WMoC2 / WVC2 electrocatalytic material was successfully prepared. After XRD phase content fitting, the mass content of the components between the two phases were WMoC2:WVC2=64.3%:35.7% respectively.
[0046] Figure 2 The linear voltammetric sweep (LSV) curves are plotted for the WMoC2 / WVC2 electrocatalytic material in a 1M KOH solution using a conventional three-electrode system. The curves are 85% IR-corrected to eliminate the effect of solution resistance on the catalytic performance test. As can be seen from the figure, only 127mV and 330mV of electrocatalytic water splitting overpotential are required, respectively, to achieve 10mA / cm 2 (η 10 ), 100mA / cm 2 (η 100 ) current density.
[0047] Figure 3 This is a scanning electron micrograph of the WMoC2 / WVC2 electrocatalytic material. As can be seen from the figure, the WMoC2 / WVC2 nanoparticles are evenly distributed.
[0048] Figure 4 This is a transmission electron micrograph of the WMoC2 / WVC2 electrocatalytic material. As can be seen from the figure, the transmission electron micrograph of the product of this example has clear heterogeneous interface lattice fringes. The lattice fringes at the edge with a lattice spacing of 0.251 nm are matched to the (100) crystal plane of WMoC2, while the lattice fringes in the other direction (with a lattice spacing of 0.244 nm) are attributed to the (111) crystal plane of WVC2.
[0049] Example 2
[0050] The preparation method of a two-phase bimetallic carbide heterostructure hydrogen evolution electrocatalyst comprises the following steps:
[0051] 1) Weigh 1.5 mmol of ammonium metavanadate, 1.5 mmol of molybdenum pentachloride, and 0.3 mmol of ammonium paratungstate and dissolve them in a mixed solution of water and ethylene glycol (volume ratio of 1:0.2, 200 ml), which is recorded as solution A.
[0052] 2) 0.25mmol hexadecyltrimethylammonium bromide, 0.25mmol hexadecyltrimethylammonium chloride, 0.8mmol glucose (C6H 12 O6) was added to solution A, heated and stirred at 60°C in a water bath for 12 h, and ultrasonicated for 30 min to obtain solution B.
[0053] 3) The prepared solution B was transferred into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 50%, the hydrothermal temperature was set to 150°C, and the reaction time was 24 hours. After the reaction was completed, the material in the reactor was collected, washed and dried to obtain powder C.
[0054] 4) Take the powder C obtained in the above step, weigh 0.5 mol of melamine (C3H6N6), fully mix it with powder C by mechanical mixing, transfer it to a low-temperature tube furnace, and calcine it under argon atmosphere at a heating rate of 5°C / min. The temperature is set to 700°C. After keeping warm for 2 hours, it is naturally cooled to obtain WMoC2 / WVC2 electrocatalytic material.
[0055] Example 3
[0056] The preparation method of a two-phase bimetallic carbide heterostructure hydrogen evolution electrocatalyst comprises the following steps:
[0057] 1) Weigh 1 mmol of ammonium metavanadate, 1 mmol of molybdenum pentachloride, and 0.5 mmol of ammonium paratungstate and dissolve them in a mixed solution of water and ethylene glycol (volume ratio 1:0.5, 100 ml), which is recorded as solution A.
[0058] 2) 0.1mmol hexadecyltrimethylammonium bromide, 0.2mmol hexadecyltrimethylammonium chloride, 1mmol glucose (C6H 12 O6) was added to solution A, heated and stirred at 60°C in a water bath for 24 h, and ultrasonicated for 30 min to obtain solution B.
[0059] 3) The prepared solution B was transferred into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 70%, the hydrothermal temperature was set to 160°C, and the reaction time was 24 hours. After the reaction was completed, the material in the reactor was collected, washed and dried to obtain powder C.
[0060] 4) Take the powder C obtained in the above step, weigh 0.05 mol of melamine (C3H6N6), fully mix it with powder C by mechanical mixing, transfer it to a low-temperature tubular furnace, and calcine it under argon atmosphere at a heating rate of 10°C / min. The temperature is set to 900°C. After keeping warm for 2 hours, it is naturally cooled to obtain WMoC2 / WVC2 electrocatalytic material.
[0061] Comparative Example 1
[0062] The method is basically the same as Example 1, except that the molar ratio of tungsten, vanadium and molybdenum in the tungsten source, vanadium source and molybdenum source is 1:1:6. After testing, the product contains W2C in addition to WMoC2 / WVC2.
[0063] During the hydrothermal preparation of precursors, improper control of the ratio of tungsten, vanadium, and molybdenum leads to the formation of monometallic carbides. Specifically, the metal precursors fail to fully mix and achieve molecular dispersion. During the subsequent high-temperature carbonization stage, locally aggregated metal atoms preferentially form monometallic carbides rather than the target bimetallic carbides. Improper control of the ratio of tungsten, vanadium, and molybdenum in the raw materials can severely impact the formation of the target bimetallic carbide composite. This imbalance manifests itself primarily in two ways: First, during the initial hydrothermal synthesis stage, metal precursors that deviate from the ideal ratio struggle to achieve uniform molecular mixing, resulting in uneven distribution of the metal components in the solution. Second, during the subsequent high-temperature carbonization process, localized excesses of one metal and deficiencies of another can lead to the formation of monometallic carbides (such as W2C, Mo2C, or VC) rather than the desired bimetallic carbide composite phases (such as WMoC2 or WVC2). This deviation from the ratio significantly reduces the formation of the bimetallic carbide heterostructure in the final product, thereby impacting the overall catalytic performance of the material.
[0064] Comparative Example 2
[0065] The process is basically the same as Example 1, except that the calcination temperature is 600° C., the calcination time is 1 hour, and the calcination atmosphere is argon.
[0066] The carbonization reaction time in this comparative example is too short, making it difficult for the bimetallic atoms to overcome the diffusion energy barrier and form an intermetallic alloy bond. Ultimately, only a single metal carbonization reaction occurs. A similar situation can also occur when the carbonization temperature is too low.
[0067] Comparative Example 3
[0068] The method is basically the same as Example 1, except that the molar ratio of vanadium to carbon in the vanadium source and the carbon source is 1:5.
[0069] The vanadium-carbon ratio of this comparative example is improperly controlled, and too little carbon source fails to fully react with the precursor, resulting in the presence of metal oxides in the material.
Claims
1. A two-phase bimetallic carbide heterostructure electrocatalyst, characterized in that: The composition of the two-phase bimetallic carbide heterostructure electrocatalyst is WMoC2 / WVC2, wherein preferably, the mass percentages of WMoC2 and WVC2 are 40% to 80% and 20% to 60% respectively.
2. The method for preparing a two-phase bimetallic carbide heterostructure electrocatalyst according to claim 1, characterized in that: The preparation method comprises the following steps: Step (1) dispersing a vanadium source, a molybdenum source and a tungsten source in a solvent to obtain a solution A; Step (2) uniformly mixing cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, glucose and solution A to obtain solution B; Step (3) subjecting solution B to a hydrothermal reaction to obtain product C; In step (4), the product C is mixed evenly with a carbon source and then calcined to obtain a two-phase bimetallic carbide heterostructure electrocatalyst.
3. The preparation method according to claim 2, characterized in that In step (1), the vanadium source is at least one of ammonium metavanadate, vanadium acetylacetonate, vanadium chloride or a hydrate thereof; the molybdenum source is at least one of molybdenum pentachloride, ammonium molybdate, sodium molybdate or a hydrate thereof; and the tungsten source is at least one of ammonium tungstate, ammonium paratungstate, tungsten chloride, sodium tungstate or a hydrate thereof.
4. The preparation method according to claim 2 or 3, characterized in that In step (1), the molar ratio of tungsten to vanadium to molybdenum among the tungsten source, the vanadium source and the molybdenum source is 1:1:1 to 6:1:
1.
5. The preparation method according to any one of claims 2 to 4, characterized in that In step (2), the molar ratio of cetyltrimethylammonium bromide to cetyltrimethylammonium chloride is 1:1 to 1:4; and the molar ratio of the total molar amount of cetyltrimethylammonium bromide and cetyltrimethylammonium chloride to glucose is 0.3 to 0.5:0.5 to 1.
6. The preparation method according to any one of claims 2 to 5, characterized in that In step (3), the temperature of the hydrothermal reaction is 150 to 200° C., and the time is 12 to 24 hours.
7. The preparation method according to any one of claims 2 to 6, characterized in that In step (4), the calcination temperature is 600-900° C., the calcination time is 2-6 hours, and the calcination atmosphere is argon.
8. The preparation method according to any one of claims 2 to 7, characterized in that In step (4), the carbon source is at least one of melamine, urea, and dicyandiamide.
9. The preparation method according to any one of claims 2 to 8, characterized in that The vanadium-carbon molar ratio of the vanadium source in step (1) and the carbon source in step (4) is 1:10 to 1:1500, preferably 1:50 to 1:
900.
10. Use of the two-phase bimetallic carbide heterostructure electrocatalyst according to claim 1 in preparing a hydrogen evolution electrode.
Citation Information
Cited By
Sub-high-entropy non-noble metal OER catalyst and preparation method thereof
CN121826761A
A catalyst, a method for preparing the catalyst, and a battery
CN122393323A
